Chronic hepatitis C: Epidemiology, viral resistance, and public health implications - Kileng, Hege (Scandinavian Journal of Gastroenterology, 2019)
Chronic hepatitis C: Epidemiology, viral resistance, and public health implications Chronic hepatitis C virus (HCV) infection can progress to cirrhosis and end-stage liver disease. The infection is frequently asymptomatic, leaving many infected individuals unaware of the diagnosis until complications occur. The total number of HCV infections is projected to remain stable or to decline, but the burden of the disease is expected to increase. Potent direct-acting antiviral therapies (DAAs) provides an opportunity to reverse the rising burden of HCV-disease. However, viral resistance to DAAs may impact their effectiveness. First, we aim to assess the prevalence of HCV infection in a general adult population. In a cross-sectional study based on data from the Tromsø 7 Study, we found a low prevalence (0.2%) of viraemic HCV infection. A substantial number (13/33) of individuals with viraemic disease were unaware of their infection. Second, we aim to estimate future complications of chronic HCV infection towards 2050 by using a Markov simulation model based on data from the Hepatitis C Study in Northern Norway. The model predicted an almost three-fold increase in the prevalence of cirrhosis (68 per 100,000), of decompensated cirrhosis (21 per 100,000) and of hepatocellular carcinoma (4 per 100,000) by 2050, as well as a six-fold increase in the cumulated number of deaths from HCV-related liver disease (170 per 100,000). Finally, we aim to investigate the effect of baseline HCV resistance-associated substitutions (RASs) on treatment outcome in patients with HCV genotypes 1a and 3 in a prospective, real-life, open label, non-randomized multi-center cohort study in Sweden and Norway. Baseline RASs appeared to be associated with lower cure rates. Our findings suggest a substantial rise in HCV-related morbidity and mortality in the coming years, despite a low prevalence of chronic HCV infection in the general population. Baseline RASs appear to impair the treatment response to DAAs in patients with genotypes 1a and 3.